2014
DOI: 10.1007/jhep02(2014)045
|View full text |Cite
|
Sign up to set email alerts
|

Topological susceptibility in lattice Yang-Mills theory with open boundary condition

Abstract: We find that using open boundary condition in the temporal direction can yield the expected value of the topological susceptibility in lattice SU(3) Yang-Mills theory. As a further check, we show that the result agrees with numerical simulations employing the periodic boundary condition. Our results support the preferability of the open boundary condition over the periodic boundary condition as the former allows for computation at smaller lattice spacings needed for continuum extrapolation at a lower computati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 33 publications
1
26
0
Order By: Relevance
“…One would like to continue these calculations to even higher lattice scale which however eventually will face the problem of efficient spanning of the space of gauge configurations. Such trapping has been already demonstrated [11]. It is interesting to investigate whether the open boundary condition can reproduce the glueball masses extracted with periodic boundary condition at reasonably small lattice spacings achieved so far and whether the former can be extended to even smaller lattice spacings.…”
Section: Motivationmentioning
confidence: 74%
See 1 more Smart Citation
“…One would like to continue these calculations to even higher lattice scale which however eventually will face the problem of efficient spanning of the space of gauge configurations. Such trapping has been already demonstrated [11]. It is interesting to investigate whether the open boundary condition can reproduce the glueball masses extracted with periodic boundary condition at reasonably small lattice spacings achieved so far and whether the former can be extended to even smaller lattice spacings.…”
Section: Motivationmentioning
confidence: 74%
“…In ref. [11], we have addressed the question whether open boundary condition in the temporal direction can yield the expected value of χ. We have shown that with the open boundary it is possible to get the expected value of χ and the result agrees with our own numerical simulation employing periodic boundary condition.…”
Section: Motivationmentioning
confidence: 99%
“…In the recent literature the problem of very long autocorrelation times and of the theoretical control over the systematic error in numerical simulations has been addressed in a series of papers [2,3,5,[7][8][9][10] and several solutions to the topological critical slowing down have been proposed [4,6,[19][20][21][22][23][24][25].…”
Section: Jhep07(2016)089mentioning
confidence: 99%
“…This corresponds to the critical slowing down occurring in statistical systems close to a second order phase transition. In addition, in these systems, a particularly dramatic increase of autocorrelation time is observed in the case of the topological charge, independently of the precise discretized definition which is used in the simulation on the lattice [1][2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last year or so the topological susceptibility of the SU(3) Yang-Mills theory has been computed by several groups on a rich set of lattices with a statistical error of a few percent [69,70,64,71]. The results are shown in the left plot of Figure 5 together with the older results obtained with the Neuberger [32] and with the spectral projector [72] Figure 5.…”
Section: First Two Cumulants Of the Charge Distribution In The Su(3) mentioning
confidence: 99%